PENGHEMATAN ENERGI MELALUI PENGGANTIAN LAMPU PENERANGAN DI LINGKUNGAN UNTAD - Baso Mukhlis (Foristek, 2011)
This study aims to determine how much influence the replacement of lighting (fluorescent or TL lamps, incandescent) with energy efficient lighting towards payment of electricity accounts Untad which has now reached an average of Rp 79,676,246 per month. Data on the number and type of lighting used in this study, obtained from the equipment Untad. From the existing datais known that fluorescent lamps 40 watts of power still dominates its use when compared with energy-saving lamps.Spread usage of these lights in the room numbering approximately 708 rooms in Untad environment. The calculation ofsavings done by looking at the difference in cost between the energy-saving lamps with other lamps for 12,000 hours oflighting the flame. Results showed that by replacing all fluorescent lamps (TL lamps), incandescent bulbs with energy-efficientlighting can reduce electricity Untad payment of Rp 4,396,015 per month or as much as Rp 52,752,180 per year. If adjusted to the age of the lamp will be a savings of USD 253,650,065 while the investment cost of energy saving light bulbs should be issued to replace the entire lamp is only about USD 144.75 million.